FDI Flows to Low-Income Countries : Global Drivers and Growth Implications. (IMF Working Papers; Working Paper ;, 2010)
What accounts for variations in FDI flows from advanced to developing countries? How have FDI inflows explained cross-country growth experiences? In this paper we tackle both these questions empirically for a large sample of middle and low-income countries. Two key results emerge: (i) lower borrowing costs and positive real-side external factors were increasingly important drivers of FDI outflows to low-income countries in the pre-crisis period; (ii) economic fundamentals, the strength of economic reforms, and commitment to macroeconomic discipline are crucial determinants of the growth dividends of FDI. Our paper suggests that low-income countries can turn to domestic policy solutions to mitigate the adverse effects of a potential decline in FDI in the post-crisis world.